AGENDA - HAMMER, MICHAEL; Aneet; Aggarwal, Monika (Gyan Management Journal, 2009)
When pioneers of global auto-industry like Ford sell marquee brands like Jaguar and Land Rover to our own Tata Motors and icons of Indian Business like Ranbaxy sell lock-stock and proudly announce their continuing co work as CEO’s under new owners it is Lime Managers understood how turbulent and unpredictable the future is for busine s toda The borderless instant world of today’s globally-exposed knowledgeable Customer is spinning at a bewildering speed. And, with 90% of scientists who have ever lived working today at full throttle, spinning- speed is rising by the second. It is for this unpredictable world that super-analytical thinker Hammer develops an Agenda for today’s Business Leaders. Fundamentals of his 9-point Agenda are: